2014
DOI: 10.1086/674899
|View full text |Cite
|
Sign up to set email alerts
|

Species Collapse via Hybridization in Darwin’s Tree Finches

Abstract: Species hybridization can lead to fitness costs, species collapse, and novel evolutionary trajectories in changing environments. Hybridization is predicted to be more common when environmental conditions change rapidly. Here, we test patterns of hybridization in three sympatric tree finch species (small tree finch Camarhynchus parvulus, medium tree finch Camarhynchus pauper, and large tree finch: Camarhynchus psittacula) that are currently recognized on Floreana Island, Galápagos Archipelago. Genetic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
175
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(182 citation statements)
references
References 93 publications
6
175
0
1
Order By: Relevance
“…Birds were mist-netted and observed in the Scalesia forest at the base of Cerro Pajas volcano (1°17′S, 90°27′W, elevation 250-350 m) (O'Connor et al, 2010a All guidebooks refer to three Darwin's tree finch species on Floreana Island: small tree finch, medium tree finch, and large tree finch (C. parvulus, C. pauper and C. psittacula, respectively). But a recent study by Kleindorfer et al (2014a) found only two genetic groups and one hybrid cluster of tree finches on Floreana Island. The hybrid offspring were the result of pairings between females of the critically endangered medium tree finch and males of the common small tree finch (Kleindorfer et al, 2014a).…”
Section: Study Locationmentioning
confidence: 96%
See 3 more Smart Citations
“…Birds were mist-netted and observed in the Scalesia forest at the base of Cerro Pajas volcano (1°17′S, 90°27′W, elevation 250-350 m) (O'Connor et al, 2010a All guidebooks refer to three Darwin's tree finch species on Floreana Island: small tree finch, medium tree finch, and large tree finch (C. parvulus, C. pauper and C. psittacula, respectively). But a recent study by Kleindorfer et al (2014a) found only two genetic groups and one hybrid cluster of tree finches on Floreana Island. The hybrid offspring were the result of pairings between females of the critically endangered medium tree finch and males of the common small tree finch (Kleindorfer et al, 2014a).…”
Section: Study Locationmentioning
confidence: 96%
“…But a recent study by Kleindorfer et al (2014a) found only two genetic groups and one hybrid cluster of tree finches on Floreana Island. The hybrid offspring were the result of pairings between females of the critically endangered medium tree finch and males of the common small tree finch (Kleindorfer et al, 2014a). At present we do not know whether hybridization extends beyond the F1 generation.…”
Section: Study Locationmentioning
confidence: 96%
See 2 more Smart Citations
“…On Daphne Island, it was the introgressive hybridization between Geospiza fortis and G. scandens-rather than conspecific gene flow with immigrants from other islands-that increased the genetic and morphological variation of resident populations and enhanced their evolutionary potential, enabling the species to more rapidly react to environmental changes [14]. In other cases, hybridization resulted in despeciation of sister species [15], or the complete disappearance of a species, as was the case for the large tree finch on Floreana island [16]. Further examples are available from the wellstudied Galápagos giant tortoises, where lineage fusion through introgressive hybridization was recently revealed on the largest island of the archipelago, Isabela.…”
Section: Introductionmentioning
confidence: 99%